Hubungan Body Image dan Eating Disorder dengan Status Gizi pada Remaja Perempuan Usia 15-18 Tahun - Zahirah, Fildza; Wirjatmadi, Bambang (Universitas Airlangga, 2024)
Background: Adolescent girls tend to have thinner bodies. Dissatisfaction with body shape can affect daily eating behavior. Misperception of body image can lead to a desire to thin out and to misbehave in diet to have an eating disorder. Bad eating behavior that lasts a long time will affect the nutritional status of adolescents. Objectives: This study aims to analyze the correlation between body image and eating disorders with the nutritional status of adolescents aged 15-18 years. Methods: This method is observational analytical research with a case-control design on 34 teenage girls in classes X and XI at Semen Gresik High School with a sampling technique using Simple Random Sampling. The instrument for measuring body image uses the Body Shape Questionnaire-34 (BSQ–34) and to assess the tendency to have eating disorders using the Eating Disorder Diagnostic Scale (EDDS). Statistical test analysis between variables uses Fisher’s exact test. Results: The results showed that there were 15 girl students (88.2%) with normal nutritional status who had a positive body image, one girl student (5.9%) who had poor nutritional status had a negative body image, along with 14 girl students (82.4%) who had normal nutritional status not tended to have eating disorders, and many as two girl students (11.8%) with underweight nutritional status tended to have eating disorders. The results of statistical test analysis show that there is no corellation between body image (p = 1,000) and eating disorders (p = 1,000) with nutritional status. Conclusions: This study concludes that no significant correlation exists between body image and eating disorders and the nutritional status of adolescent girls aged 15-18 years.